Variation in the Occurrence of fimA Genotypes of Porphyromonas gingivalis in Periodontal Health and Disease - Manohar Kugaji (International Journal of Environmental Research and Public Health, 2020)
Porphyromonas gingivalis is regarded as a “keystone pathogen” in periodontitis. The fimbria assists in the initial attachment, biofilm organization, and bacterial adhesion leading to the invasion and colonization of host epithelial cells. The present study aimed to investigate the occurrence of fimA genotypes in patients with chronic periodontitis and healthy individuals in the Indian population, and to study their association with the number of P. gingivalis cells obtained in subgingival plaque samples of these subjects. The study comprised 95 samples from the chronic periodontitis (CP) group and 35 samples from the healthy (H) group, which were detected positive for P. gingivalis in our previous study. Fimbrial genotyping was done by PCR and PCR-restriction fragment length polymorphism (RFLP). The fimA type II was more prevalent in the CP group (55.89%), followed by type IV (30.52%), whereas in the H group, type I was the most prevalent fimbria (51.42%). The quantity of P. gingivalis cells increased with the presence of fimA types II and III. Our results suggest a strong relationship between fimA types II and IV and periodontitis, and between type I and the healthy condition. The colonization of organisms was increased with the occurrence of type II in deep periodontal sites, which could play an important role in the progression of the disease.